Chemotherapy Bells and Liminality in Advanced Cancer Care - Stone, Alyson (Anthropologica, 2025)
Ringing a bell at the end of chemotherapy treatment has become a pervasive practice across cancer centres in Canada and the US. The ritual fails to accommodate the unique position of patients diagnosed with advanced cancer who may remain on chemotherapy treatment up to the end of life. Drawing on 17 months of fieldwork in a Canadian cancer hospital and classical liminality scholarship, I argue that the modern proliferation of cancer treatments produces a liminal space, an ambiguous territory that exists between the hope for a cure and the imminence of death. I show how patients’ liminal status becomes concealed by the bell ringing ceremony. While the ritual is meant to signal transition to reincorporation, it inspires ambivalence on the part of advanced cancer patients precisely because, for them, the end of chemotherapy does not translate as aggregation into the cancer-free world. Witnesses such as nurses, family, and friends should be aware of the bell’s heavy symbolism attached to patients’ uncertain futures and recognize that a myriad of conflicting reactions are possible. The focus on treatment keeps patients in an extended time of illness, preventing them from preparing for the end of life.